Aneurysms Associated with Brain Arteriovenous Malformations - Rammos, S.K.; Gardenghi, B.; Bortolotti, C.; Cloft, H.J.; Lanzino, G. (American Journal of Neuroradiology, 2016)
SUMMARY: Brain arteriovenous malformations are frequently associated with the presence of intracranial aneurysms at a higher-than-expected incidence based on the frequency of each lesion individually. The identification of intracranial aneurysms in association with AVMs has increased due to improvement in diagnostic techniques, particularly 3D and superselective conventional angiography. Intracranial aneurysms may confer a higher risk of hemorrhage at presentation and of rehemorrhage in patients with AVMs and therefore may be associated with a more unfavorable natural history. The association of AVMs and intracranial aneurysms poses important therapeutic challenges for practicing neurosurgeons, neurologists, and neurointerventional radiologists. In this report, we review the classification and radiology of AVM-associated intracranial aneurysms and discuss their clinical significance and implications for treatment.IAintracranial aneurysm